2017
DOI: 10.1016/j.algal.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Note to Editor: Microalgae cultivation for wastewater treatment and biofuel production: a bibliographic overview of past and current trends

Abstract: This is a repository copy of Note to Editor: Microalgae cultivation for wastewater treatment and biofuel production: a bibliographic overview of past and current trends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…To this end, gaining a better understanding of the interactions between specific microalgae and protozoa will help to develop operational strategies that minimize crashes. Species of the genera Chlorella and Tetradesmus are common in freshwater ecosystems and are among the most used and best understood microalgae [22][23][24]. Here, specific strains of the species Chlorella vulgaris and Tetradesmus obliquus were selected to conduct the experiments, which also allowed their differentiation by light microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, gaining a better understanding of the interactions between specific microalgae and protozoa will help to develop operational strategies that minimize crashes. Species of the genera Chlorella and Tetradesmus are common in freshwater ecosystems and are among the most used and best understood microalgae [22][23][24]. Here, specific strains of the species Chlorella vulgaris and Tetradesmus obliquus were selected to conduct the experiments, which also allowed their differentiation by light microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms either cooperate through the exchange of extracellular metabolites, vitamins, and siderophores to increase nutrient uptake rates and biomass productivities, or compete by metabolite excretion to produce bactericidal or micro-algicidal effects ( Cydzik-Kwiatkowska and Zielińska, 2016 ). Consistently, the research pathway in this scientific field has been directed towards the use of two different medium cultures: non-sterilized wastewater (NSWW) and sterilized wastewater (SWW) ( Unc et al, 2017 ). The few studies that exist on this topic have shown that MBC nutrient removal efficiencies vary significantly depending on which medium they grow on; as NSWW contains natural micro-fauna that does not exist in SWW.…”
Section: Introductionmentioning
confidence: 99%
“…These high natural amounts of oxygen enhance the active aerobic bacteria to oxidize organic matter, resulting in the production of the inorganic nutrients NH 3 , PO 4 3− , and CO 2 , which are essential for algal growth. Moreover, WSPs can be operated using a very low bacterial population, within the range of 10 6 to 10 7 CFU/mL [25][26][27]. Furthermore, the treatment efficiency and microalgal-bacterial function rely on several factors, such as dissolved oxygen, pH, sunlight, and pond design [21].…”
Section: Introductionmentioning
confidence: 99%